MOTIVASI DAN PERSEPSI WISATAWAN YANG BERKUNJUNG KE DAYA TARIK WISATA PANTAI PENIMBANGAN DI KABUPATEN BULELENG - Luh Putu Pusparini; Putu Agus Prayogi; Ni Wayan Mekarini (Universitas Triatma Mulya, 2022)
The purpose of this study was to determine the motivation and perceptions of tourists visiting the tourist attraction of Penimbangan Beach in Buleleng Regency. The research method used in this research is descriptive qualitative. In this study, data collection was carried out by observation, interviews with resource persons, and distributing questionnaires to 55 tourists using incidental sampling technique in which 31 statements down. The questionnaire given consists of thirteen statements regarding tourist motivation which refers to the theory of push and pull motivation. These push factors and pull factors are actually internal and external factors that motivate tourists to make decisions to travel, as well as eighteen statements regarding tourist perceptions that refer to the Tourism Destination Attributes theory (4A), namely attraction, amenities, accessibility and ancillary services. The research found out 2 conclusions, such as (a) aspect of push and pull motivations that get the highest score are because visitors want to do recreation while swimming and to visit modern spot as well as contemporary hangouts. (b) Meanwhile, the perception of tourists on the attributes of tourist destinations (4A) in the tourist attraction of Penimbangan Beach in Buleleng Regency is that Penimbangan Beach is one of the unique tourist attractions, equipped with adequate facilities, very easy access to achieve, but not yet supported by sources of information and organization but still incomplete tourist attraction management.